Overdue : the misadventure of Bob the book [book with audioplayer] - Koster, Gloria (VOX Books, 2024)
Meet Bob. He's the all-time favorite library book at Wisdom Hill Elementary. But Sebastian is nothing like Bob's previous enthusiastic borrowers. In fact, Sebastian completely forgets about Bob! Will Bob ever feel the love of a contented fan again, or will he be lost and alone forever? In this harrowing tale told from a book's point of view, author and librarian Gloria Koster showcases the joy of reading and the importance of taking care of books. --